Penerapan Kedisiplinan Terhadap Kinerja Karyawan PT. Sembilan Jaya Farm - Diah Laraswati; Acep Samsudin; Erry Sunarya (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
Every company always wants its employees to have a good discipline attitude, with disciplined activities within a company can run smoothly, directed. And can more easily complete the work. Discipline reflects that the employee has good performance. Because good employee performance can be assessed if the employee meets or obeys the rules that are enforced by the company. Research or research conducted at PT. Nine Jaya Farm Sukabumi. The purpose of this study was to determine how much the influence of discipline on employee performance at PT. Sembilan Jaya Farm Sukabumi with a population of employees at PT. Sembilan Jaya Farm with 80 respondents using probability sampling and saturated sample techniques. In this study using validity and reliability testing. Data collection techniques used in primary data are questionnaires and interviews along with secondary data is a literature study. And the data analysis technique used is the normality test, the correlation coefficient test, the coefficient of determination test, a simple linear regression test and a hypothesis test that is the t test. The results of this study show that there is an influence of discipline in obeying the regulations on employee performance at PT. Nine Jaya Farm by proving the results of testing the hypothesis or t test showed more t counts than the table that is as much as 5031> 1.6646